The act of face-saving: apology strategies among Meranaw university students in southern Philippines - Juhaid H. H. Abbas; Binnor M. Abdul Samad; Mohammad Hussein Imam; Annie Mae Berowa (Indonesian Reseacher for Language Learning and Teaching, 2026)
The present study demonstrates the pattern of the speech act of apology among Meranaw university students in Southern Philippines, who are adherents of Islam, by employing a descriptive qualitative research method. The study specifically aims to illustrate the strategies employed by 41 respondents in realizing the speech act of apology, as well as to examine the apology strategies they employed towards different groups of addressees: superior status; equal status; lower status; friends; and strangers. The data were collected through a modified written discourse completion task (DCT) that contains 16 hypothetical scenarios. The 615 data obtained were mainly coded and analyzed using the taxonomy of apology strategies and treated using frequency and percentage counting. Finally, the study reveals that the respondents generally and dominantly employ the explicit Expression of Apology (EA) strategy. In addition, combinations of apology strategies as well as new strategies employed by the respondents do not conform to the social status and social distance variables and there is no notable difference in strategy found.